Making sense of reasons: prospects for an interpretivist account of practical reasons - Beesley, David (2011)
This thesis investigates the prospects for an interpretivist account of practical reasons. The proposed account identifies practical reasons with sets of propositional attitudes from which certain actions follow, given the constraints of interpretable functioning. Following Davidson, these constraints are taken to be enumerated by formal decision theory and formal semantics. Thus the account of practical reasons is framed in terms of what rationally follows from agents' beliefs and desires. The hope is that an account of practical reasons of this kind can explain the existence of practical reasons without invoking irreducible normative properties or relations. This outcome depends upon the availability of a theory of (radical) interpretation which is free from prior normative commitments. It is argued that a non-normative reading of Davidson's theory of radical interpretation is available, such that the account of practical reasons can meet this requirement. Although the proposed account of practical reasons does not admit of the possibility of categorical reasons for action, the ensuing objection that it fails to allow for the possibility of moral reasons for action is resisted. It is suggested that a plausible account on which moral reasons are hypothetical in kind can be provided. In particular, an account of moral reasons which is framed in terms of the motivations associated with a capacity for empathic affect is advanced. More generally, the aspiration of the thesis is to provide an account of practical reasons framed in terms of the requirements of interpretable functioning which will be regarded as an interesting and credible naturalistic option.